Implementation of the Inquiry-Oriented RADEC Learning Model - Nurul Saadah Agustina; Wahyu Sopandi; Atep Sujana (Postgraduate, University of Mataram, 2024)
The experiment activities carried out are not complete experiment activities. One of the learning models that includes investigative activities is the RADEC learning model. This research aims to implement inquiry-oriented RADEC learning. The method used in this research mixes methods by design-embedded experimental design. The subjects in this study were 45 elementary school students in class V, one of the elementary schools in Bandung Regency. Data collection techniques were collected using test and non-test instruments in the form of observation sheets, test questions, and questionnaires. Each stage of the RADEC learning model was good, with some stages increasing at each meeting and some optimally implemented. In investigative activities, students still need guidance in designing and making investigative reports and are required more than once to develop their skills in compiling, carrying out, and reporting investigations. Besides that, RADEC learning can increase students' mastery of concepts and encourage student collaboration skills.